The Challenger disaster - McNeese, Tim. (New York, NY : Scholastic Inc., 2003)
Recounts events surrounding the explosion of the space shuttle Challenger in 1986, the first shuttle to carry a civilian passenger, and discusses the impact of this disaster on the United States space program.
Includes bibliographical references (p. 46) and index.
G12
Keywords: Challenger (Spacecraft) -- Accidents -- Juvenile literature; Challenger (Spacecraft) -- Accidents; Space vehicle accidents -- United States -- Juvenile literature; Space shuttles -- Accidents